Handling objects with very wet skin reduce variability during precision grip task. (11th June 2019) - Kandaswamy, Deepa; Murthy, Muthukumar; S, Mahasampath Gowri; Alexander, Mathew; Krothapalli, Srinivasa Babu
Highlights: Very wet skin reduces the variability in precision grip task than dry skin condition. Moisture on fingertips to be considered for using precision grip as a diagnostic tool for patients with hand dysfunction. Extent of moisture decides the strategy of grip force to be applied during object manipulation in precision grip task. Abstract: Several extrinsic factors affect precision grip task variability. Presence of moisture in glabrous skin can regulate the impact of extrinsic factors. Consequently, wetness may influence the precision grip task variability per se by regulating its force, rate and time parameters. This study aims to examine the influence of age, coefficient of skin friction (CF) and object weight (extrinsic factors) on precision grip task variability in dry skin condition (DSC) and very wet skin conditions (VWSC). Eighty healthy subjects performed precision grip task with four different weights (1.3N, 1.4N, 1.5N, and 1.7N) sequentially in DSC and VWSC. Simple and multiple linear regression analysis were performed to estimate the independent and combined effect of extrinsic factors on precision grip parameters. Our results show that the extent of variability caused by the extrinsic factors on precision grip task significantly reduced when objects were held with VWSC than DSC. Wetting of the skin also decreased standard deviation and coefficient of variation of friction. The frictional range of individuals was widespread in DSC (0.62–3.42) while VWSC brought it to a closer range (0.77–1.64). Our findings suggest that wetness of skin reduces precision grip task variability, and further knowledge on this may help in designing precision grip as a quantitative screening tool for patients with hand dysfunction.